Global Metabolomic Characterizations of Microcystis spp. Highlights Clonal Diversity in Natural Bloom-Forming Populations and Expands Metabolite Structural Diversity - Le Manach, Séverine; Duval, Charlotte; Marie, Arul; Djediat, Chakib; Catherine, Arnaud; Edery, Marc; Bernard, Cécile; Marie, Benjamin (Frontiers in Microbiology, 2019)
Cyanobacteria are photosynthetic prokaryotes capable of synthetizing a large diversity of secondary metabolites exhibiting noticeable bioactivity or genuine toxicity. Microcystis constitutes one of the most common cyanobacteria taxa forming intensive blooms that nowadays arise worldwide in freshwater ecosystems. They can produce numerous cyanotoxins (i.e. toxic cyanobacterial metabolites), which could be harmful to human health and aquatic organisms. To better understand the variations in cyanotoxins production between clones of the Microcystis, we investigated the diversity of 24 strains isolated from the same blooms, from different populations in various geographical area. Strains were compared by genotyping with 16S-ITS fragment sequencing and metabolites chemotyping using LC ESI-qTOF mass spectrometry. While genotyping can only discriminate between the different species, the global metabolomes reveal clear discriminant molecular profiles between strains. These profiles can be clustered primarily according to their global metabolite content, then to their genotype, and finally to their sampling localities. A global molecular network of all metabolites highlights the production of a wide set of chemically diverse metabolites, among which few microcystins, but also many aeruginosins, microginins, cyanopeptolins and anabaenopeptins, along with a large set of unknown molecules. These components constitute the molecular biodiversity that still remain to be investigated at their structural as well as at their potential bioactivity (e.g. toxicity) levels.